Pengaruh Sikap Orang Tua Terhadap Minat Menjadi Guru Pada Mahasiswa Jurusan Pendidikan Ekonomi Universitas Negeri Padang - Tika Junita; Dessi Susanti (Jurnal Salingka Nagari, 2023)
The purpose of this study is to determine the impact of parents' attitudes on students' interest in becoming teachers in Economic Education. This is survey research that employs quantitative research methods. This study's population consists of Economics Education students from the Faculty of Economics of Universitas Negeri Padang from 2017 to 2021, with up to 85 students selected as samples. In this study, probabilistic sampling with proportional stratified random sampling was used. Simple linear regression analysis was used to analyze data that had previously been tested for conventional assumptions, normality tests, linearity tests, heterogeneity tests, and hypothetical t-tests. According to the findings of this study, parents' attitudes have a significant impact on their children's desire to become teachers.